Ahistorical Study of Kurdish Alliance under the Leadership of Bader Khan - Salim Mahmud, Salah Muhammed (Journal of Duhok University, 2019)
The idea of Prince Badrakhan's leadership of the alliance between the Kurdish Emirates was the result of the political and military circumstances that Province Bhutan witnessed. The incident of the attack of the forces of the Emirate of Suran on the province of Bhutan , Rashid Pasha attack on the city of Al-Jazera in 1834 , the loss of the Ottoman army in the battle of Nazib 1839 ,and events that followed this stage were main reasons that  prompted Prince Badrakhan to think of a Kurdish alliance aimed at resisting Ottoman policy based on ending the rule of the Kurdish Emirates.The Kurdish alliance was established in the 1840s, after a close relationship between Prince Badrakhan and Khan Mahmud, especially after the decision of the Ottoman Empire to separate Sangak Bhutan from the state of Diyarbakir and annex it to Mosul in 1842. This caused the tension between Prince Badrakhan and Muhammad EnjaBirkdar, the governor of Mosul, prompting Prince Badrakhan to approach Kurdish figures such as Khan Mahmud, NurallahBek and others to ally against the Ottoman Empire. Prince Badrakhan also gained the support of the most influential clerics, including Sheikh Taha al-Nahari in the Hakkari region, Sheikh Yusuf Zakho and Sheikh Muhammad Haruri, in order to support his idea of establishing the Kurdish alliance.